A Segretaria Nazionale dei fasci all´estero, a NSDAP-Auslandsorganisation, o servicio exterior de la falange e as políticas externas dos partidos fascistas no entre-guerras. O caso latino-americano - João Fábio Bertonha (Nuevo mundo - Mundos Nuevos, 2017)
In the period between the two world wars, many parties and fascist movements had its own foreign policy, embodied in party institutions as the fasci all'estero, the NSDAP-AO, the Servicio Exterior de la Falange and others.These organizations had as a central function to gather the nationals living abroad and to spread the fascist ideology among them. They were used as instruments for controlling of opponents who have taken refuge beyond national borders and for propaganda among emigrants and also foreigners. Finally, in many cases, they exercised spying or information gathering functions and served as privileged channels for contacts with supporters and friends abroad.The purpose of this paper is to present the main fascist transnational networks working in the Latin American continent, namely the Italian, German and Spanish, and discuss their similarities and differences. In addition, it will seek to address their influence and importance in the formation of native fascism and the relationship between them. Finally, the paper tries to deal with the Latin-American network of the parties and fascist movements, mainly the Integralism´s Secretariado Nacional de Relações com o Exterior.